PHYSICAL COURAGE IN JAMES DASHNER’S NOVEL THE MAZE RUNNER - Ali Sadikin Brutu; Muhammad Amrin Siregar (JOURNAL OF LANGUAGE, 2020)
This research is concerned with Protagonist’s Physical Courage found in James Dashner’s novel The Maze Runner first published in 2009. It is described in the novel that the Protagonist of the novel has shown his physical courage in a Glade which is always haunted or attacked by dangerous creatures called Grievers. Because of his great courage, he has been able to influence his friends to fight with the Grievers. He is even admired by his friends, all the Gladers. He can even finally be able to escape together with them to live freely outside the place that has already imprisoned them in it. This research uses a qualitative research method proposed by Creswell: defining this method as a means for exploring and understanding the meaning individuals or group ascribe to a social or human problem. After having analyzed the variable in the novel, it can be concluded that the protagonist shows two forms of physical courage. They are selfishness and being one own-self.